Metode Iqra’ Sebagai Sarana Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa SDIT Da’i Qur’an Padang Birik-Birik Kota Pariaman - Yani, Putri Andri; Saputra, Edriagus; Andrianto, Andrianto; Afnita, Nora (Journal Education And Islamic Studies, 2024)
This study aims to analyse the planning, implementation process, evaluation, and factors that influence the use of the Iqra' method in improving the ability to read the Qur'an at SDIT Da'i Qur'an. This research uses a qualitative approach with descriptive method. Data were collected through observation, interviews, and documentation, then analysed in depth. The results showed that: first, the planning of learning Iqra‘ method begins with the establishment of specific learning objectives, the selection of materials that are in accordance with the ability of students, and the provision of Iqra’ books for each student. Second, the implementation of learning includes the introduction of hijaiyah letters, stringing letters, the introduction of punctuation marks such as mad, tanwin, sukun, waqaf, and tajweed terms. Third, the evaluation is done by observing and listening to students' reading during the learning session, where students are asked to repeat the reading until they achieve fluency without tajweed and makhraj errors. Fourth, there are supporting factors, such as adequate learning modules, teachers‘ ability to apply the Iqra’ method, and parental support. However, some inhibiting factors were identified, such as limited facilities and infrastructure, as well as students' low interest in learning who are more likely to play.